2013
DOI: 10.1177/1471301213485374
|View full text |Cite
|
Sign up to set email alerts
|

The experience of sons caring for a parent with dementia

Abstract: This study explored the experiences of sons caring for a parent with dementia. Individual, semi-structured interviews were conducted with a purposeful sample of sons (n = 13) in a rural part of Ireland. Interviews were audiotaped, transcribed verbatim and analysed for common themes. The key themes that emerged were 'the parental bond', 'a binding role', 'coordinating care and support' and a 'getting on with it' approach to care. The study highlighted the commitment of sons to their caregiving role and the stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(90 citation statements)
references
References 48 publications
2
87
0
1
Order By: Relevance
“…The NILS does not provide information on the health of the care recipient or on their relationship with the caregiver; however, previous studies found these to influence the mental health of caregivers (Etters et al . , McDonnell & Ryan ). Our data did supply some information on multimorbidity of the household and the analysis adjusted for this.…”
Section: Discussionmentioning
confidence: 96%
“…The NILS does not provide information on the health of the care recipient or on their relationship with the caregiver; however, previous studies found these to influence the mental health of caregivers (Etters et al . , McDonnell & Ryan ). Our data did supply some information on multimorbidity of the household and the analysis adjusted for this.…”
Section: Discussionmentioning
confidence: 96%
“…Participants' constant worry, as well as sense of failure, guilt, frustration, distress, and resentment are also considered important aspects of psychological well-being in the literature (Carers Trust, 2011;Steptoe et al, 2015) (McDonnell & Ryan, 2014;Santos, Sousa, Ganem, Silva, & Dourado, 2013). Older carers coping strategies, such as having positive view about their situation or having increased spirituality, were also been identified in other qualitative investigations as mitigating factors of negative feelings people with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Whether an ICP enlists the system to provide direct assistance (e.g., activity prompting), retrieve care-related information, and coordinate care between AAL and multiple care partners, the decision and process by which ICPs entrust care to another party cannot be taken for granted. For instance, while an ICP may find caring stressful or burdensome, he or she may also ascribe significant meaning to their care roles; they may derive a sense of pride or view caring as a natural continuation of bonds with PwDs [10, 12, 52–54]. Such mixed feelings may lend themselves to fluctuating preferences for AAL support, depending on moods, stress levels, and current circumstances.…”
Section: Discussionmentioning
confidence: 99%